Sex/gender differences in gastrointestinal endoscopy from the perspective of patients and gastroenterologists - Nayoung Kim (Korean Society of Gastrointestinal Endoscopy, 2023)
The sex/gender of gastroenterologists impact patients' satisfaction, compliance, and clinical outcomes. For instance, female gastrointestinal (GI) endoscopist-patient gender concordance improves health-related outcomes. This finding suggests that it is important to increase the number of female GI endoscopists. While the number of women in the field of gastroenterology is increasing in the United States and Korea by over 28.3%, it is not enough to account for the gender preferences of female patients. GI endoscopists are at a high risk of endoscopy-related injuries. However, there is a different distribution of muscle and fat; male endoscopists are more affected in their back, while females are more affected in the upper extremities. Women are more susceptible to endoscopy-related injuries than men. There is a correlation between the number of colonoscopies performed and musculoskeletal pain. Job satisfaction is lower in young female gastroenterologists (30' and 40') than in the opposite gender and other ages. Thus, it is important to address these issues in the development of GI endoscopy.